2021
DOI: 10.1093/jxb/erab105
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study and transcriptome comparison reveal novel QTL and candidate genes that control petal size in rapeseed

Abstract: Petal size determines the value of ornamental plants, and thus their economic worth. However, the molecular mechanisms controlling petal size remain unclear in most non-model species. To identify quantitative trait loci and candidate genes regulating petal size in rapeseed (Brassica napus), we performed a genome-wide association study (GWAS) using data from 588 accessions over three consecutive years. We detected 16 significant single nucleotide polymorphisms (SNPs) associated with petal size, with the most si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…This model states that under the assumption of polygenic architecture for phenotypic traits and random mating, gene frequencies would be close to Hardy–Weinberg equilibrium and phenotypic variation among individuals of a single species would tend to be normally distributed 73 . While we do not know the genetic architecture of any of the traits included in our study, analyses in other plants show that some of these traits are indeed polygenic 74 , 75 . We assume that a similar genetic architecture is present in Escallonia , and therefore that the pattern of variation of such traits can be reasonably described with Gaussian distributions.…”
Section: Methodsmentioning
confidence: 69%
“…This model states that under the assumption of polygenic architecture for phenotypic traits and random mating, gene frequencies would be close to Hardy–Weinberg equilibrium and phenotypic variation among individuals of a single species would tend to be normally distributed 73 . While we do not know the genetic architecture of any of the traits included in our study, analyses in other plants show that some of these traits are indeed polygenic 74 , 75 . We assume that a similar genetic architecture is present in Escallonia , and therefore that the pattern of variation of such traits can be reasonably described with Gaussian distributions.…”
Section: Methodsmentioning
confidence: 69%
“…The core difference between GLM, MLM and CMLM is whether to control the kinship matrix K, and many studies have found that controlling K may lead to severe false negatives (Tibbs et al, 2021). To confirm the reliability of SNP loci in our study, the multi-locus GWAS (ML-GWAS) method with high detection power also needs to be considered, such as the study on the petal size of rapeseed (Qian et al, 2021). Generally, the number of significant SNPs associated with phenotypes by ML-GWAS was comparatively higher than those in the SL-GWAS model.…”
Section: Gwas Of Flower Lotusmentioning
confidence: 92%
“…For example, an SNP in the PPR gene was linked to flowering time leading to early-and late-flowering pearl millets (Diack et al, 2020). In another example, both known and novel genes associated with petal size were identified in rapeseed (Qian et al, 2021). Some flower color variants were also identified by GWAS case studies.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed methods used for SNP genotyping and mapping were previously described [ 46 , 47 , 48 ]. In brief, DNA libraries with a mean insert size of 350 bp were constructed, and 125 bp paired-end reads were generated using an Illumina HiSeq 4000 instrument at the Biomarker Technologies Corporation (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…napus seeds has been challenging. In this study, we performed a genome-wide association study for six glucosinolate metabolites in 143 rapeseed accessions using 239,945 SNP markers obtained by resequencing [ 46 , 47 , 48 ]. Our goals were to identify candidate genes to enrich the metabolic regulatory network of the GSL biosynthesis pathway, and to lay a foundation for the breeding of B. napus with improved quality.…”
Section: Introductionmentioning
confidence: 99%